Estrategias de marketing para la reactivación hotelera de la ciudad de Babahoyo, Provincia de Los Ríos - Moyano Bajaña, Joselin Lilibeth (2020)
Given the scenario that currently crosses all the countries of the world that have been hit by the Covid-19 pandemic, which is an infectious disease caused by the Coronavirus, this disease was unknown before the outbreak broke out in Wuhan (China) in December 2019 Returning to normality by way of an economic reactivation becomes a great global challenge, especially due to the scarcity of opportunities to offer a tourist destination in the city of Babahoyo, due to the impact that the pandemic called coronavirus is leaving. This case study analyzed the strategies for the reactivation of the hotel sector in the city of Babahoyo, belonging to the province of Los Ríos. For the collection of information in this case study, it was carried out with the qualitative and quantitative method through field, exploratory, descriptive, documentary and bibliographic research and with the techniques of the survey and indirect observation, which allowed to know the strategies that They will help for a reopening in the hotel establishments.